Early Childhood Educators in Promoting Quality ECCE Students: A Case Study Jigawa State - Ibrahim, Baffa Bashari; Abdullahi, Auwalu; Ringim, Iliyasu Ibrahim (Jurnal Riset Madrasah Ibtidaiyah, 2025)
This paper examines the Impact of Early Childhood Educators in Promoting Quality ECCE Students in Colleges of Education Jigawa State (Nigeria). This paper examines the importance of quality education which Nigeria as a nation needs a functional educational system that can equip learners with requisite knowledge, attitudes and skills to enable them relate and adapt successfully to the rapid socio- economic, cultural and political changes in the society. To achieve quality education, Nigeria Government has to recognize the role of Early childhood educators in promoting Quality education to students of Colleges of Education in Jigawa State (Nigeria). The paper recommends that, there is need for creation of conducive teaching and learning environment with the provision of appropriate, well-equipped and adequate laboratories, workshops, classrooms, libraries, staff offices, as well as good and adequate hostel and classroom accommodation, teaching and learning techniques in Colleges of Education of Nigeria.